Spatial Extent of Fluorescence Quenching in Mixed Semiconductor–Metal Nanoparticle Gel Networks. (1st June 2021) - Rosebrock, Marina; Zámbó, Dániel; Rusch, Pascal; Pluta, Denis; Steinbach, Frank; Bessel, Patrick; Schlosser, Anja; Feldhoff, Armin; Hindricks, Karen D. J.; Behrens, Peter; Dorfs, Dirk; Bigall, Nadja C.
Abstract: In this work, mixing and co‐gelation of Au nanoparticles (NPs) and highly luminescent CdSe/CdS core/shell nanorods (NRs) are used as tools to obtain noble metal particle‐decorated macroscopic semiconductor gel networks. The hybrid nature of the macrostructures facilitates the control over the optical properties: while the holes are trapped in the CdSe cores, the connected CdSe/CdS NRs support the mobility of excited electrons throughout the porous, hyperbranched gel networks. Due to the presence of Au NPs in the mixed gels, electron trapping in the gold NPs leads to a suppressed radiative recombination, namely, quenches the fluorescence in certain fragments of the multicomponent gel. The extent of fluorescence quenching can be influenced by the quantity of the noble metal domains. The optical properties are monitored as a function of the NR:NP ratio of a model system CdSe/CdS:Au. By this correlation, it demonstrates that the spatial extent of quenching initiated by a single Au NP exceeds the dimensions of one NR, which the Au is connected to (with a length of 45.8 nm ± 4.1 nm) and can reach the number of nine NRs per Au NP, which roughly corresponds to 400 nm of total electron travel distance within the network structure. Abstract : It is demonstrated that a single gold nanoparticle is able to quench the fluorescence of up to nine semiconductor nanorods in mixed, co‐gelated gel networks. Upon varying the particle number ratio of CdSe/CdS and Au nanocrystals, the spatial extent of quenching, thus, the travel distance of photoexcited electrons is changed within the interconnected semiconductor backbone.